2021
DOI: 10.1177/10892532211002382
|View full text |Cite
|
Sign up to set email alerts
|

Regional Analgesia for Cardiac Surgery. Part 2: Peripheral Regional Analgesia for Cardiac Surgery

Abstract: The introduction of regional analgesia in the past decades have revolutionized postoperative pain management for various types of surgery, particularly orthopedic surgery. Nowadays, they are being constantly introduced into other types of surgeries including cardiac surgeries. Neuraxial and paravertebral plexus blocks for cardiac surgery are considered as deep blocks and have the risk of hematoma formation in the setting of anticoagulation associated with cardiac surgeries. Moreover, hemodynamic compromise res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…Cardiac surgery requires anticoagulants, and it is not widely accepted due to concerns about neuraxial hematoma following anticoagulants. 1 , 14 , 21 , 22 , 23 , 24 , 25 , 26 A few trials have demonstrated the safety of regional anesthetic and analgesic techniques in the context of possible anticoagulation during cardiac surgery. 1 , 19 Regional blocks have enormous potential to be integrated into hospitals' acute pain management paradigms following cardiac surgery, given their initial success in decreasing pain scores and reducing opiate usage.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac surgery requires anticoagulants, and it is not widely accepted due to concerns about neuraxial hematoma following anticoagulants. 1 , 14 , 21 , 22 , 23 , 24 , 25 , 26 A few trials have demonstrated the safety of regional anesthetic and analgesic techniques in the context of possible anticoagulation during cardiac surgery. 1 , 19 Regional blocks have enormous potential to be integrated into hospitals' acute pain management paradigms following cardiac surgery, given their initial success in decreasing pain scores and reducing opiate usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 1 , 19 Regional blocks have enormous potential to be integrated into hospitals' acute pain management paradigms following cardiac surgery, given their initial success in decreasing pain scores and reducing opiate usage. 26 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Devarajan et al explored evidence behind the use of various neuraxial and non-neuraxial regional analgesic techniques in a two-part review. 6,7 It is clear that epidural blocks will not be re-entering the cardiac surgical arena because of concerns over epidural hematoma, despite their advantages. However, spinal opioids are making a comeback, with renewed interest in their clinical use and research for ERAS protocols.…”
Section: Is It Time For Paradigm Shift In Painmentioning
confidence: 99%
“…There are several regional analgesia options for cardiac surgery pain management: peridural analgesia, paravertebral block, erector spinae plane (ESP) block, serratus plane block and PECS II block. These techniques were enhanced by comprehensive utilization of ultrasound guidance, the latter being cost-effective, readily accessible, reliable imaging and having multiple advantages [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%